An investigation into the school experiences of HIV-positive secondary school learners on ARV treatment in Katutura, Windhoek - Haipinge, Emilie (Rhodes University, Faculty of Education, Department of Education, 2013)
What are the school experiences of HIV-positive secondary school learners on ARV treatment? Although the provision of life-saving antiretroviral (ARV) treatment is central in the medical and policy response to the HIV pandemic, relatively little research (in the SADC region and in Namibia particularly) attends to people's experiences and the social effects of taking ARV treatment. This study probed the experiences of high school learners on ARV treatment in Khomas Region, Namibia. As researcher I used a qualitative case study design based mainly on interviews with a purposive, select sample of eight learners at the school where I am a teacher-counsellor. Methods used also included: observations; focus group interviews with eight teachers at the site school; a questionnaire survey with Life Skills teachers from 25 schools in the Khomas Region; and document analysis. Using a theory of health-related stigma and discrimination as well as perspectives on resilience and agency as conceptual and analytical lenses, this study found that only a handful of these learners were living openly with HIV and AIDS. Being both HIV-positive and on ARV medication was a double bind for learners facing pervasive stigma and discrimination in and out of school. Discourses associated with HIV and AIDS, sex, and sexuality shaped people's response to them and they feared being 'caught out'. Here the study explores the complex reciprocal relationship between cause and effect in stigma, showing some consequences for these learners: isolation (both voluntary and imposed), mental anguish, depression and suicidal leanings; also (at school) absenteeism, grade repetition and dropout. Distinguishing stigma from discrimination in this study enabled insight into actual practices that constrain learner participation and inclusion in and out of school. Trust between learners on ARVs and teachers proved to be low. Teacher respondents not only felt unequipped to deal with the psychosocial needs of learners on ARVs but also indicated that confronting these needs animated their personal vulnerability (around HIV-related experiences in their own families). However, hopeful patterns also emerged. Some mediatory factors out of school shaped these learners' experiences and identities positively, with implications for in-school experiences and participation. Some learner journeys reflected shifts from deep despair towards the emergence of voice, positive self-concepts and resilient dispositions. Here, also, this study enters a neglected area of research, showing how the complex interplay of learners' own agency with social support brought these positive outcomes. Most learners had experienced rejection from immediate family, receiving support rather from community members who became 'family'. The study thus also raises pressing questions on the nature of support structures (both in and out of school) in contexts shaped by HIV and AIDS, where stigma and discrimination are pervasive and where stable family structures, parental oversight and 'normal' progression through school cannot be assumed. It recommends that schools gain better insight into how learners' circumstances shape their experiences, and develop internal policies, procedures and networks to reduce stigma and discrimination against HIV-positive learners on ARV treatment, as well as. ensuring material, medical, emotional, and psychological support for them.
Keywords: HIV-positive youth -- Namibia -- Katutura (Windhoek); HIV-positive youth -- Social conditions -- Namibia -- Katutura (Windhoek); HIV infections -- Social aspects -- Namibia -- Katutura (Windhoek); HIV infections -- Psychological aspects -- Namibia -- Katutura (Windhoek); AIDS phobia -- Namibia -- Katutura (Windhoek); Antiretroviral agents